2021
DOI: 10.46328/ijtes.242
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Robotic Applications on Academic Achievement: A Meta-Analysis Study

Abstract: In this study, it was aimed to investigate the experimental studies regarding the effect of educational robotic applications on academic achievement by the meta-analysis method. Within the scope of the research, the studies carried out on educational robotic applications were scanned from national and international databases and selected according to inclusion criteria. The sample of the study consisted of 2606 participants with 1300 in the experimental group and 1306 in the control group. In the study, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…It was discovered how well using educational robots can improve the mathematical and engineering skills of elementary school children. According to this study, the employment of educational robots in the classroom had a positive impact on students' engineering mathematics skills (Talan, 2021) and the results regarding the integration of educational robotics into math lessons corroborate previous studies. The data obtained shows how employing instructional robots can help students to strengthen their mathematical and engineering skills while also advancing the field of instructional robotics with a beneficial new technique.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was discovered how well using educational robots can improve the mathematical and engineering skills of elementary school children. According to this study, the employment of educational robots in the classroom had a positive impact on students' engineering mathematics skills (Talan, 2021) and the results regarding the integration of educational robotics into math lessons corroborate previous studies. The data obtained shows how employing instructional robots can help students to strengthen their mathematical and engineering skills while also advancing the field of instructional robotics with a beneficial new technique.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, students' dexterity improved, and the course was made more engaging by permitting the use of rich and readily available material, so the students were able to learn while having fun, which increased their learning (Lopez-Caudana et al, 2020;Negrini et al, 2023). However, other studies, such as Çakır, Korkmaz, İdil, and Erdoğmuş (2021) and Talan (2021) suggest that the engineering and mathematical skills of educational robots have not significantly improved, or have not significantly differed from other studies. Overall, the results of the study show a significant relationship between the students' engineering mathematics skills and demonstrate that learning with the educational robot greatly improved their skills in critical and analytical thinking, the ability to represent geometric shapes using equations, applying geometric transformations to modify and manipulate shapes and objects, applying mathematical skills to real-life geometric problems, developing problem-solving skills in geometry through training and practical application, and understanding counting, addition, subtraction, multiplication, and division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous studies that have found similar conclusions about the impact of educational robotics on students' performance. For example, a meta-analysis conducted by Talan [39] examined the effects of educational robotics in STEM fields and found that it improves students' problem-solving and critical thinking skills but does not have a significant effect on academic scores. Similarly, another study by Ferrarelli and Iocchi [40] on the integration of educational robotics in a science course showed that while students improved their understanding of physical concepts through robotics, this improvement was not significantly different from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the usefulness and effectiveness of ER in the education of typical students in general (Benitti, 2012;Mubin et al, 2013;Beltrametti et al, 2017;Athanasiou et al, 2018;Talan, 2021), but only a few have already explored the use of ER with special needs students (Damiani et al, 2013;Businaro et al, 2014;Agatolio et al, 2016). ER can be utilised as a tool to promote individual development, creativity, teamwork, and communication, as well as problem-solving and computational reasoning (Kandlhofer & Steinbauer, 2016;Rubinacci et al, 2017).…”
Section: Rationale Of the Researchmentioning
confidence: 99%